PERANCANGAN ULANG KURSI KULIAH YANG ERGONOMIS DI FAKULTAS TEKNIK UNIVERSITAS PEMBANGUNAN NASIONAL "VETERAN" JAKARTA MENGGUNAKAN METODE ERGONOMIC FUNCTION DEPLOYMENT - Bisma Kadarbani Hariarto, - (2019)
In teaching and learning activities, adequate facilities are needed, especially lecture chairs used by students. However, with the existing conditions students will experience physical fatigue that is characterized by achiness characterized by fatigue and aches in some parts of the body. This is partly due to the sitting position of students who have to work with non-ergonomic lecture chairs. The purpose of this study is to design an ergonomic lecture chair with ergonomic anthropometry, RULA (Rapid Upper Limb Assessment) and EFD (Ergonomic deployment system) approach to increase comfort, and reduce fatigue, and the negative impacts caused by uncomfortable sitting positions by focusing on the design of lecture chairs that are adjusted to size / student body dimensions. The chair is designed to have a backrest and a writing pad that can be adjusted to the user liking (Adjustable) and a padded seat with foam. with 4 legs and leg support to ensure stability with a base height of 42 cm, width of base 44 cm, width of backrest 40 cm, length of base 46 cm, height of backrest 50 cm, height of writing pad 24 cm, and length of writing pad 26 cm.